Estrategias de lectura comprensiva para potenciar el valor del respeto del bloque curricular 6 rimas y cuentos o cuentos y rimas en el área de lengua y literatura, de los niños y niñas del quinto grado de educación general básica de la unidad educativa Fernando Suárez Palacio del barrio Carigán, parroquia Sucre de la ciudad de Loja, período lectivo 2013-2014 - Díaz Eras, Gloria Juliana (2015)
This research work entitled: COMPREHENSIVE READING STRATEGIES TO ENHANCE THE VALUE OF RESPECT FOR BLOCK CURRICULUM 6 RHYMES AND STORIES OR STORIES AND RHYMES IN THE AREA OF LANGUAGE AND LITERATURE OF THE CHILDREN OF THE FIFTH DEGREE OF GENERAL EDUCATION BASIC UNIT EDUCATIONAL FERNANDO SUAREZ PALACIO DEL BARRIO CARIGÁN, PARISH SUCRE CITY LOJA, LECTIVO PERÍODO 2013-2014, has the general objective: to determine reading comprehension strategies as essential to strengthen their knowledge by the value of respect for students in fifth element degree of General Basic Education Unit Fernando Suarez Palace. The methods used for the structure of this research work were quasi-experimental cross-sectional design, comprehensive, analytical, synthetic method, participatory assessment, models or proactive, workshop and comprehensive evaluation method as techniques used: the surveys at 21 students and a teacher for the fifth grade of general basic education, information with the application of the instruments have obtained the teacher does not use strategies to understand a text, lack of motivation for reading, so that the student has a poverty or lack of vocabulary, lack of prior knowledge, deficiencies in decoding, do not apply in class values, which negatively influences the students do not have adequate behavior and meaningful learning. It is concluded that the model application strategies by the researcher through the workshop method directly benefited students and teachers, helping to reduce the difficulties presented by the students in the development of reading comprehension to enhance the value of respect shown using Pearson's r. The application of reading comprehension strategies help to better learning and understanding to promote the value of respect.